1988
DOI: 10.1111/j.1365-2818.1988.tb01409.x
|View full text |Cite
|
Sign up to set email alerts
|

STM of layered‐structure semiconductors

Abstract: SUMMARY We have used scanning tunnelling microscopy to characterize the layered structure semiconductors MoS2, WSe2 and SnS2. Atomically resolved images as well as spectroscopic data in both tunnelling directions have been obtained for the cleaved surfaces of these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Physically, MoS 2 possesses a larger lattice constant than graphite (3.16 versus 2.46 Å). [57][58][59] Further, MoS 2 is a semiconductor whose surface structure is primarily comprised of Mo d z 2 and S p z orbitals. 58,59 (In contrast, graphite has C p z orbitals protruding out of the plane of the surface.)…”
Section: "Single Chemical Markers" In Stmmentioning
confidence: 99%
See 2 more Smart Citations
“…Physically, MoS 2 possesses a larger lattice constant than graphite (3.16 versus 2.46 Å). [57][58][59] Further, MoS 2 is a semiconductor whose surface structure is primarily comprised of Mo d z 2 and S p z orbitals. 58,59 (In contrast, graphite has C p z orbitals protruding out of the plane of the surface.)…”
Section: "Single Chemical Markers" In Stmmentioning
confidence: 99%
“…[57][58][59] Further, MoS 2 is a semiconductor whose surface structure is primarily comprised of Mo d z 2 and S p z orbitals. 58,59 (In contrast, graphite has C p z orbitals protruding out of the plane of the surface.) Combined, these effects have been reported to lead to interesting changes in monolayer order.…”
Section: "Single Chemical Markers" In Stmmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical experiments indicate that the band gap of 2H-MoSz is actually indirect with a gap of _.1.25 eV[31]. Scanning tunneling microscopy (STM) experiments also show the presence of a 1.35 eV indirect gap in 2H-MoSz[32]. During the course of this study, it was found possible to increase the size of the theoretical band gap by increasing the contribution ez of the more diffuse Mo 4d double zeta STO.…”
mentioning
confidence: 72%
“…Researches of CSs obtained under UHV for MoS 2 , WSe 2 , SnS 2 [11], and GaSe [12] cleavage surfaces using the methods of LEED, STM, and ultra-violet photoelectron spectroscopy [9] testify to the absence of hexagonal systems of unsaturated electron bonds on the CSs of layered crystals. The corresponding electron spectra of CSs weakly differ from the bulk ones [9,13] and the "pattern" of the surface plane, i.e.…”
Section: Introductionmentioning
confidence: 99%